Surgical lung biopsy for interstitial lung disease: a two center propensity score matching analysis - Grott, Matthias; Wimmer, Cosmas D.; Kreuter, Michael; Prasse, Antje; Eichhorn, Martin E.; Eichhorn, Florian; Herth, Felix; Seeliger, Benjamin; Kriegsmann, Katharina; Schmidt, Werner; Koenigsfeld, Katharina; Zardo, Patrick; et al. (Respiration, 2022)
Background: Surgical lung biopsy (SLB) is recommended for patients with nonclassified interstitial lung disease (nILD) if high resolution computed tomography and/or transbronchial lung biopsy did not achieve a definitive diagnosis. Current literature suggests better patient tolerability and less postoperative complications if surgery is performed under spontaneous ventilation. Objectives: We conducted a propensity score matching (PSM) analysis of our nILD patients undergoing SLB under spontaneous ventilation or general anesthesia to investigate postprocedural AE-ILD, 30-/90-day mortality and perioperative variables in two academic high-volume centers (Hannover, Heidelberg). Methods: All patients undergoing SLB for nILD under general anesthesia (GAVATS) and spontaneous ventilation (NIVATS) at both centers from February 2013 until April 2021 were analyzed retrospectively. Data of 132 patients were used for PSM resulting in 40 pairs. Results: There was one death in the NIVATS group 60 days after SLB and one AE-ILD in each cohort. Chest tube indwelling time, chest tube total effusion, length of hospital stay, and operative time were all in favor of NIVATS. Conclusions: In our PSM analysis, NIVATS is associated with faster postprocedural recovery. However, a reduction in postoperative AE-ILD or 30-/90-day mortality was not observed.
Gesehen am 07.02.2023